Mejoramiento de ingeniería de un sistema de contención de suelos para una plataforma petrolera ubicada en la Provincia de Orellana, utilizando herramientas de gestión medioambientales y de seguridad en el trabajo - Paredes Andrade, Estuardo Rafael (2014)
The Ecuadorian Amazon has been always characterized by high levels of humidity, this is a serious problem in construction field, because the soil has significant rates of water into its components, leading to landslides caused by rain or filtration, it becomes an important phenomenon in this region. The main purpose of this paper is to present a modern system called soil containment wall screens, which are being constructed on top of piles of steel pipeline, introduced to soil layer by using a method called piloting. This wall is designed to protect an oil platform called ASIRI 31against landslides occurred in the area in recent months.